Identification of pyroptosis‐related clusters for prediction of overall survival and characterization of tumor microenvironment infiltration in laryngeal squamous cell carcinoma. Issue 1 (22nd March 2023) - Du, Wei; Xia, Xueming; Yu, Jiayun; Shao, Bin
Abstract: Laryngeal squamous cell carcinoma (LSCC) accounts for one‐third of head and neck squamous carcinoma (HNSCC). Although improvements have been made in treatments, the prognosis of patients with LSCC is unsatisfactory. Pyroptosis creates an environment that inhibits tumor growth in various cancers, but pyroptosis regulation in the tumor immune microenvironment in LSCC remains little known. The Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases were used to collect clinical traits and gene expression data of LSCC patients. We present a systematic overview of the immune microenvironment of LSCC based on genetics and transcriptional profiles of pyroptosis‐related genes (PRGs) and divide 220 LSCC into three distinct PRGclusters. Based on the three survival‐related PRGs identified in Lasso‐penalized Cox regression, samples from the training and validation cohorts were divided into two discrete geneClusters. We construct a prognostic model based on Risk score, quantify pyroptosis level and link it with patient outcome. Furthermore, we verified the expression level of one prognostic gene Basic Leucine Zipper ATF‐Like Transcription Factor at the tissue level in the validation experiment. These findings reveal the crucial role of pyroptosis and can assist in predicting patient prognosis, guiding optimal treatment choices, and developing new immunotherapies for LSCC. Abstract : We present a systematic overview of the immune microenvironment of laryngeal squamous cell carcinoma (LSCC) based on genetics and transcriptional profiles of pyroptosis‐related genes (PRGs) and construct a prognostic model based on the Risk score. These findings can assist in predicting patient prognosis, guiding optimal treatment choices, and developing new immunotherapies for LSCC.